Taxonomic study on the photid amphipods (Senticaudata, Corophiida, Photoidea, Photidae) from Korean waters, with descriptions of a new genus and seven new species - Tae Won Jung; Charles Oliver Coleman; Seong Myeong Yoon (ZooKeys, 2019)
In this paper, seven new species of the family Photidae from Korean waters are described and illustrated in detail. Among them, Exiliphotis petila sp. nov. is a monotype of the newly reported Exiliphotis gen. nov., which is characterized by slenderer and more elongate pereopods 5–7 than those of other genera of the family Photidae. The genus Latigammaropsis is reported for the first time from Korean waters based on the description of Latigammaropsis careocavata sp. nov., which is differentiated from other Gammaropsis group by having weakly sexual dimorphic gnathopods 2, those have simple palmar margins in both sexes. Three new species of Photis are also described: Photis bronca sp. nov., Photis posterolobus sp. nov., and Photis longicarpus sp. nov. The formerly misidentified Photis longicaudata from Japan and China as well as the Korean material could be classified as a new species, P. bronca sp. nov. For that, the syntypes of P. longicaudata were re-examined, and lectotype and paralectotypes were newly designated in this study. Photis bronca sp. nov. is characterized by quadrate tooth on the palmar margin medially on gnathopod 2 in both sexes. Photis posterolobus sp. nov. shows a pointed posterior lobe on the ischium and a well-developed process of the propodus on male gnathopod 2. Photis longicarpus sp. nov. can be distinguished from other species of the genus by very elongate carpus of male gnathopod 1. Two new species belonging to the genus Podoceropsis are also reported: Podoceropsis insinuomanus sp. nov. has a strongly bisinuous palmar margin on male gnathopod 2, and Podoceropsis pseudoclavapes sp. nov. differs from the closely related species of Podoceropsis clavapes by different shape of the palmar margin and shorter dactylus of male gnathopod 2. Additionally, a key to the Korean species of Photidae is provided.